ChemInform Abstract: Facile One‐Pot Synthesis of 1, 3, 5‐Trisubstituted Pyrazoles from α, β‐Enones. Issue 1 (January 2015) - Yu, Jin; Kim, Ko Hoon; Moon, Hye Ran; Kim, Jae Nyoung
Abstract The title compounds (III) are obtained by efficient one‐pot synthesis from α, β‐enones and arylhydrazine hydrochlorides.